The Realization of Formulaic Expressions in EFL Teacher-Student Classroom Interactions - Lia Indriyani; Dwi Rukmini; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2022)
Formulaic expressions are essential for developing students' communicative competence to speak English naturally and fluently. This research aimed to determine how the EFL teachers and students used the five types of formulaic expressions in their classroom interactions. This study is discourse analysis, particularly conversation analysis, using a qualitative research approach. The research subjects were two teachers and thirty-one students from two different EFL classes in a private high school in Semarang. The data were obtained by recording their 5x40 minutes' classroom interactions. The video recordings were transcribed and then observed. After all of the data were collected, they were classified and analyzed based on Biber et al.'s (1999) framework and then described qualitatively. The study results showed that the teachers and the students realized all five types of formulaic expressions; lexical bundles, idiomatic phrases, free combinations of verb+particle, binomial expressions, and inserts. It shows that the teachers and the students are able to speak relatively natural English. By doing the further analysis, it was also found that even though the teachers used the formulaic expressions a lot more than the students, the orders of the frequency of formulaic expressions used are similar, as well as some expressions used. Surprisingly, it was revealed that there were some expressions which were not used by the teachers but were realized by the students.